PELAKSANAAN PELAYANAN OLEH TENAGA KEFARMASIAN BERDASARKAN PERATURAN MENTERI KESEHATAN REPUBLIK INDONESIA NOMOR 30 TAHUN 2014 TENTANG STANDAR PELAYANAN KEFARMASIAN DI PUSKESMAS (Studi di Puskesmas Kabupaten Purbalingga) - R. Adi Soeprijanto (MIH Unsoed, 2018)
Pharmaceutical service is an integrated activity with a view to identifying, preventing, and resolving drug related issues. Limited number of pharmacist, misappropriation of drugs, availability of drugs and legal certainty of contract pharmacist are inhibiting factors of pharmaceutical services at Public Health Center.This research is in the form of juridical normative-empirical by using secondary and primary data. Secondary data source from library study as secondary legal materials and primary data source from observation and interview as primary legal material.The results showed pharmacist is responsible for pharmaceutical services in Public Health Center, both clinical pharmacy and drug management. Drug shortages occur because the stock is empty from district health office and the presence of expired drugs comes from provincial stock buffer. Technical implementation of pharmaceutical service using guidelines in accordance with legislation. Appointment of contract worker by unauthorized persons caused administrative violations. Registration certificate and practice license are the basic of legal certainty for pharmacist.